2001
DOI: 10.1046/j.1471-6712.2001.00035.x
|View full text |Cite
|
Sign up to set email alerts
|

The baby was the focus of attention – first‐time parents’ experiences of their intimate relationship

Abstract: The baby was the focus of attention - first-time parents' experience of their intimate relationship. The purpose of this study was to describe the phenomenon of 'first-time parents' intimate relationship', to focus on their mental health, and the ability to support them professionally. Ten Swedish parents (five couples) were interviewed on two occasions, when the first baby was 6 and 18 months old, respectively. A descriptive phenomenological method was used. The findings show that the essence of the phenomeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
87
1
12

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(107 citation statements)
references
References 15 publications
7
87
1
12
Order By: Relevance
“…Acknowledging time and energy as a cause for changing the expression of sexuality was common for all men and illustrated in earlier studies (Ahlborg and Strandmark, 2001;St John et al, 2004;Williamson et al, 2008). The limited time and often lacking energy created a focus on acknowledging each other through every day life and both previous research and this study confirm a new form of togetherness to evolve between the partners after having a child (Premberg et al 2008).…”
Section: Discussionsupporting
confidence: 70%
“…Acknowledging time and energy as a cause for changing the expression of sexuality was common for all men and illustrated in earlier studies (Ahlborg and Strandmark, 2001;St John et al, 2004;Williamson et al, 2008). The limited time and often lacking energy created a focus on acknowledging each other through every day life and both previous research and this study confirm a new form of togetherness to evolve between the partners after having a child (Premberg et al 2008).…”
Section: Discussionsupporting
confidence: 70%
“…The fathers in this study reflected on parental education in light of their experiences of complicated birth; however, fathers with experiences of normal birth might have reflected differently on the parental education and formed other conceptions. The fathers in the present study focused on their baby and their involvement as a parent, as has previously been described (Ahlborg & Strandmark, 2001;Ahldén et al, 2008). Although the sample size is small, the findings highlight these fathers' conceptions, mapping the potential for parental education involving both parents in group activities and lecturing (Ahldén et al, 2008).…”
Section: Discussionmentioning
confidence: 55%
“…The fathers expressed their initial difficulty in finding enough time to focus on their relationship with their partner and that may have impaired their relationship. However, prior research has indicated that this strain seems to be true, not only for the parents of preterm infants (Stjernqvist, 1992), but also for those of full-term infants (Ahlborg & Strandmark, 2001;Hall, 1995). Fagerskiold (2006) showed, in a Swedish study, that fathers of full-term infants had similar needs to mothers with regard to the support provided by healthcare nurses and it is to be assumed that the same is true for fathers of very preterm infants, not only after discharge, but also during the NICU period.…”
Section: Discussionmentioning
confidence: 99%